Engaging Community Partners to Understand and Respond to Substance Use and Addiction Crisis Facing Families in Prince Albert, Saskatchewan. (September 2022) - Maina, Geoffrey; Ogenchuk, Marcella; Sherstobitoff, Jordan; Bratvold, Robert; Robinson, Barbara
Substance use is a persisting health care crisis that has led to residents' addiction to diverse substances in Prince Albert, Saskatchewan. This public health issue affects not only those with a substance use disorder but also those within their circle of family and friends. This paper aims to outline the community engagement processes that we undertook to identify community priorities for addressing the substance use and addiction issues facing them. We began the community engagement using a patient-oriented research process, which led to the development of a grant application. Following the awarding of this grant application by the Saskatchewan Health Research Foundation and Saskatchewan Centre for Patient-Oriented Research, we conducted interviews with family members affected by addiction in the city. The study provided us with significant insight into the impacts of substance use disorders on family members. The importance of collaboration among people with lived experience, health care providers, and community partners helped us to identify our research questions. Community members also actively participated in the data collection, analysis, and presentation of the findings where priorities for the interventions were identified. The conversations we had because of the community's engagement and participation in the research process enhanced our understanding of the realities of caring for people with substance use disorders and the importance of family involvement throughout the process. We also learned lessons regarding community engagement and participation in research on a stigmatizing and complex topic.